Intervensi Penguatan Membaca Kritis melalui Debat Literasi Berbasis Deep Learning dengan Teks Autentik-Digital pada Website Edukasi di SMA Kota Kediri - Andri Pitoyo; Sujarwoko Sujarwoko; Risa Helilintar; Sherly Nur Azizah; Siiti Chalimatus Sa'diyah (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study developed and tested an integrative learning model to improve the critical reading skills of high school students in Kediri City through a deep learning approach, authentic digital texts, and literacy debates based on educational websites. Using a quasi-experimental design with a pretest-posttest control group, it involved 240 eleventh-grade students from eight high schools in three subdistricts. The t-test confirmed a significant difference (p < 0.001). This model effectively improves the ability to analyze, evaluate, and synthesize information, supporting 21st-century literacy, the “Merdeka Belajar” (Freedom of Learning) vision, and SDG 4 on quality education. This research provides an empirical solution to the low level of critical literacy in Indonesia and has the potential to become a reference for education policies that are responsive to global challenges.